2007
DOI: 10.1055/s-2006-958466
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic Effects of Prostasomes Isolated from Prostatic Cancer Cell Lines and Seminal Plasma

Abstract: Thromboembolism is well recognized as a major complication of cancer. Many tumor cells overexpress tissue factor (TF), which activates blood coagulation in cancer patients. Inflammatory cells expressing TF are also contributors to this activation. In prostate cancer, we believe that prostasomes may also be involved in the initiation of blood coagulation. Prostasomes are submicron secretory granules derived from the prostate gland. They are surrounded by membrane and their extracellular appearance and membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Nonetheless, previous surgeries and disease progression are strongly associated with an increased risk of TED and should be accounted for when assessing the impact of ADT on TED [1][2][3][4][5][6][7][8][9][10]. In our previous study, we observed an increased risk of TED in men with PCa on ADT compared with the general Swedish male population, although a number of health and lifestyle factors could not be accounted for [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, previous surgeries and disease progression are strongly associated with an increased risk of TED and should be accounted for when assessing the impact of ADT on TED [1][2][3][4][5][6][7][8][9][10]. In our previous study, we observed an increased risk of TED in men with PCa on ADT compared with the general Swedish male population, although a number of health and lifestyle factors could not be accounted for [2].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery and disease severity are known to increase the risk of thromboembolic disease (TED) in men with prostate cancer (PCa) [1][2][3][4][5][6][7][8][9]. The risk of TED is further enhanced in men with PCa treated with androgen deprivation therapy (ADT) [1,2,10,11]; however, it is unknown to what extent ADT influences the risk of TED when accounting for previous surgeries and disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Babiker and colleagues 37 showed that the early release of prostasomes from prostate cancer cells into the circulation might evoke blood-clotting effects causing thromboembolic disease. Another study by Li and colleagues 16 showed a possible link between endocrine treatment and thromboembolic disease, in which they noted that the prevention of experimental arterial thrombosis by the use of androgens at physiological concentrations is mediated by the androgen receptor through modulation of platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…Cells from prostate cancer and its metastases both produce and release prostasomes, which differ quantitatively rather than qualitatively from their normal counterparts. As in other cancers, human prostate carcinoma constitutively overexpress TF and prostasomes derived from these cancer cells vehicle larger amounts of TF [18]. A similar mechanism, involving TF-bearing microvesicles that arise from tumor cells or monocytes, characterizes the thrombophilic state of patients with other types of cancer [14,19,20].…”
Section: Abnormal Blood Constituentsmentioning
confidence: 99%